Las potencias emergentes en la arquitectura regional - Wagner, Christian (Revista Mexicana de Política Exterior, 2022)
Based on evidence of the participation of emerging powers in the major regional forums and institutions, Christian Wagner makes a comparative analysis of the degree of power or influence Brazil, Russia, China, India and South Africa (brics) wield in their respective regions and asks just how important regional architecture is to them in terms of their global aspirations. Wagner believes brics can, for all intents and purposes, be deemed powers in their respective regions, but it is not clear that this has contributed to their rise or their global objectives. It is easy to identify material inequalities in the economic and military prowess of these five countries and their neighbors, and draw conclusions as to the power and influence of each, but on the political arena, which would presuppose recognition of their regional leadership, it is not evident how much power they can actually harness. With the exception of Russia and China, which are permanent members of the un Security Council, emerging powers are continually subject to opposition in their respective regions. In any case, concludes Wagner, the participation of rising powers in the regional architecture remains vital when it comes to addressing transnational problems such as migration, terrorism, the trafficking of drugs and people and environmental issues, regardless of the discernible economic benefits.